Investigating Sustainable NGO–firm Partnerships: An Experimental Study of Consumer Perception of Co-Branded Products - Laura Therese Heinl (MDPI AG, 2021)
With crises like climate change and degradation of the earth’s natural habitats, human consumption needs to become more sustainable to decrease humanity’s environmental footprint. Fostering sustainable consumer behavior by enabling consumers to make an informed choice for sustainable products is vital in changing human consumption for the better. To optimize consumers’ perception of sustainable products, companies can establish partnerships with environmental non-governmental organizations (NGOs). In practice, retailers and NGOs can engage in NGO–firm co-branding of sustainable products. Yet, little is known about the impact of this NGO–firm co-branding on consumer perception. We fill this gap based on a 2 × 2 × 2 experimental study. We test consumers’ trust, product and brand perception of co-branded sustainable products. Our study finds that NGO–firm co-branding has a significant positive effect on all the above. The effect is moderated by familiarity with the co-branding partnership and consumer attitudes. We discuss how those NGO–firm partnerships can be a useful tool to guide customers to more sustainable consumption choices. The results are discussed in light of sustainability communication and cross-sector partnership theory. We offer important insights for consumer perspectives on sustainability communication, business engagement of NGO–firm partnerships and develop future research ideas for consumer behaviour.